Fraction Sense Mahasiswa dalam Perspektif Visualisasi dan Estimasi - Wulandari, Nourma Pramestie; Lu'luilmaknun, Ulfa; Triutami, Tabita Wahyu; Novitasari, Dwi (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Fraction sense is a critical aspect of number sense, particularly for prospective mathematics teachers. This study aims to describe students’ fraction sense from two main perspectives: visualization and estimation strategies. The study employed a qualitative descriptive method involving 80 fourth-year mathematics education students. Data were collected through a fraction sense test and semi-structured interviews. The findings indicate that students’ overall fraction sense was moderate, with an average score of 37.2. Students demonstrated higher performance in estimation strategies (68%) compared to visual representation tasks (32%). Many students struggled to interpret visual fraction models, especially when presented in unfamiliar forms such as non-standard diagrams or number lines. The results suggest that students' thinking remains procedural and lacks conceptual flexibility. Therefore, it is recommended that visual representation be more explicitly integrated into teaching practices as a tool to support estimation and foster meaningful fraction sense.